A kind of high-efficiency adsorption injection activated carbon and preparation method thereof

By using red pine wood to prepare and activate activated carbon, and by acid-base treatment and addition of iron ions, the problem of insufficient adsorption performance of activated carbon pore structure is solved, and more efficient adsorption performance and medicinal carbon quality is achieved.

CN118637612BActive Publication Date: 2025-02-14福建韩研环保科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410675204.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-29
Publication Date
2025-02-14
Estimated Expiration
2044-05-29

AI Technical Summary

Technical Problem

The existing activated carbon for injections may damage the pore structure during the preparation process, resulting in a decrease in pore ratio and affecting adsorption performance.

Method used

Red pine wood is used as raw material, and the adsorption of activated carbon is enhanced by two activations of carbon dioxide and water vapor, and the ash is removed by impregnation of acids and alkalis to avoid damaging the carbon structure. At the same time, ferrous sulfate heptahydrate and ferrous chloride hexahydrate were added to enhance the activity and adsorption properties of activated carbon.

Benefits of technology

The specific surface area, total pore volume and microporous volume of activated carbon are improved, and the adsorption performance is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004863815380000101
    Figure BDA0004863815380000101
Patent Text Reader

Abstract

This invention relates to a highly efficient activated carbon for adsorbing injections and its preparation method, belonging to the field of activated carbon technology. The invention discloses a method for preparing highly efficient activated carbon for adsorbing injections, using red pine wood as raw material to produce red pine raw material carbon. During the preparation of the highly efficient activated carbon for adsorbing injections, it undergoes two activation processes with carbon dioxide and water vapor, enhancing the adsorption capacity of the activated carbon. Simultaneously, acid and alkali impregnation removes ash without damaging the carbon structure. The activated carbon after deashing treatment further increases its specific surface area, total pore volume, and micropore volume, meeting the quality requirements for pharmaceutical-grade activated carbon. Furthermore, the addition of ferrous sulfate heptahydrate and ferric chloride hexahydrate forms iron ions in the pores of the activated carbon and loads them on its surface, thereby enhancing the activity and adsorption performance of the activated carbon.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of activated carbon and relates to a high-efficiency adsorption injection activated carbon and a preparation method thereof. Background Art

[0002] Activated carbon for injection is a special purpose activated carbon. It is widely used in the purification, decolorization, purification and refining of finished and semi-finished products such as Chinese and Western APIs, pharmaceutical intermediates, chemical APIs, and biopharmaceuticals because of its fast adsorption speed, good decolorization effect, improved purity, increased drug stability, and avoidance of drug side effects. In the production of infusion, medical activated carbon is an indispensable auxiliary material. In addition to filtering impurities, it is also often used to remove "pyrogens" when preparing liquid medicines.

[0003] The adsorption performance of activated carbon for injection is closely related to its pore structure. In the adsorption process, only when it enters the filled pores can it play an effective adsorption role, realize the filtering and impurity removal of raw materials, purification, decolorization, refining and absorption of intestinal pathogens and toxins. The surface area of ​​activated carbon for injection includes the internal surface area and the external surface area. In fact, it is the huge internal surface area that plays the main adsorption performance. During the preparation process, the minerals contained in the raw materials are concentrated in the activated carbon for injection to become ash, the main components of which are silicon and alkali metal salts. After acid and alkali treatment, the ash content can be greatly reduced. However, the pore structure of the activated carbon may be damaged in this process, resulting in a decrease in porosity. Summary of the invention

[0004] The present invention relates to a highly efficient adsorption injection activated carbon and a preparation method thereof, and belongs to the field of activated carbon technology. The present invention discloses a preparation method of highly efficient adsorption injection activated carbon, wherein red pine wood is used as a raw material to prepare red pine raw carbon, and in the process of preparing highly efficient adsorption injection activated carbon, carbon dioxide and water vapor are activated twice to enhance the adsorption of the activated carbon, and at the same time, the acid and alkali are impregnated to remove ash without destroying the structure of the carbon, and the specific surface area, total pore volume, and micropore volume of the activated carbon after deashing are further increased to meet the quality requirements of medicinal carbon. In addition, ferrous sulfate heptahydrate and ferric chloride hexahydrate are added to form iron ions in the pores of the activated carbon and load its surface, thereby enhancing the activity of the activated carbon and enhancing the adsorption performance.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] A method for preparing highly efficient adsorption injection activated carbon, the method comprising the following steps:

[0007] (1) crushing red pine wood with a pulverizer, drying it in a drying oven, and then sieving it to obtain a raw material powder, placing the raw material powder in a fluidized bed, introducing nitrogen and heating it, heat-insulating it for carbonization, then replacing the nitrogen with carbon dioxide for heat-insulating activation, and cooling it to room temperature to obtain red pine raw material carbon;

[0008] (2) mixing red pine raw carbon with potassium hydroxide, adding deionized water and stirring to mix, impregnating in a polytetrafluoroethylene digestion tank at a constant temperature, and then drying in a blast drying oven, and then washing with deionized water until neutral and drying to obtain carbon powder a;

[0009] (3) Then, boric acid is added and mixed, and the mixture is placed in a polytetrafluoroethylene digestion tank at a constant temperature and then dried in a blast drying oven, and washed with deionized water until neutral to obtain pretreated red pine raw material carbon;

[0010] (4) Pre-treating the raw red pine carbon under the protection of nitrogen, then removing the nitrogen and introducing water vapor for activation, closing the water vapor valve, then opening the nitrogen valve, cooling to room temperature to obtain water vapor activated red pine carbon, then adding distilled water and polyethyleneimine to mix and ultrasonically treating to form liquid red pine carbon;

[0011] (5) Add ethanol to liquid red pine carbon to form a mixed solution, then add ferrous sulfate heptahydrate while stirring, then add ferric chloride hexahydrate, add ammonia water to adjust the pH value after stirring, heat and stir, dry, and cool to obtain a high-efficiency adsorption injection activated carbon.

[0012] Furthermore, in the step (1), the drying temperature is 180-200°C, the sieving mesh size is 200-300 mesh, the temperature and time of the heat preservation carbonization are 300-600°C and 1-2h respectively, and the temperature and time of the heat preservation activation are 400-500°C and 2h respectively.

[0013] Furthermore, in step (2), the mass ratio of the Korean pine raw carbon to potassium hydroxide is 2-4:1, the solid-liquid ratio of the total mass of the Korean pine raw carbon and potassium hydroxide to deionized water is 10-50:1 g / L, and the temperature and time of the constant temperature immersion are 20-30°C and 20-24h, respectively.

[0014] Furthermore, in the step (3), the solid-liquid ratio of carbon powder a to boric acid is 1:2-4 g / mL, wherein the mass concentration of boric acid is 8%, and the temperature and time of the constant temperature immersion are 40-50° C. and 8-10 h, respectively.

[0015] Furthermore, the heating in step (4) refers to heating to 700-900° C., and the activation time is 80-100 min.

[0016] Furthermore, in the step (4), the solid-liquid ratio of steam-activated red pine carbon to distilled water is 1:10 g / mL, the volume ratio of distilled water to polyethyleneimine is 100:0.05-1, and the ultrasonic time is 3-5 h.

[0017] Furthermore, in step (5), the volume ratio of liquid red pine carbon to ethanol is 1.5:1, wherein the mass concentration of ethanol is 75%, and the mass contents of ferrous sulfate heptahydrate and ferric chloride hexahydrate in the mixed solution are 3.0-3.5% and 8.2-8.5%, respectively.

[0018] Furthermore, in the step (5), the molar concentration of the ammonia water is 0.1 mol / L, the pH value is 7, and the time and temperature of the heating and stirring are 2-3 h and 80-100° C., respectively.

[0019] Beneficial effects of the present invention:

[0020] 1. The present invention uses red pine wood as raw material to make red pine raw material carbon, and in the process of preparing high-efficiency adsorption injection activated carbon, it is activated twice by carbon dioxide and water vapor, and the adsorptivity of activated carbon is enhanced. At the same time, the impregnation of acid and alkali plays the role of removing ash and will not destroy the structure of carbon. The activated carbon specific surface area, total pore volume and micropore volume after deashing are further increased, and the quality requirement of medicinal carbon is met. In addition, ferrous sulfate heptahydrate and ferric chloride hexahydrate are added to form iron ions in the activated carbon pores and load its surface, thereby enhancing the activity of activated carbon and enhancing adsorption performance. DETAILED DESCRIPTION

[0021] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with embodiments.

[0022] Example 1

[0023] A method for preparing highly efficient adsorption injection activated carbon, the method comprising the following steps:

[0024] (1) crushing red pine wood with a pulverizer, drying it in a drying oven, and then sieving it to obtain a raw material powder, placing the raw material powder in a fluidized bed, introducing nitrogen and heating it, heat-insulating it for carbonization, then replacing the nitrogen with carbon dioxide for heat-insulating activation, and cooling it to room temperature to obtain red pine raw material carbon;

[0025] (2) mixing red pine raw carbon with potassium hydroxide, adding deionized water and stirring to mix, impregnating in a polytetrafluoroethylene digestion tank at a constant temperature, and then drying in a blast drying oven, and then washing with deionized water until neutral and drying to obtain carbon powder a;

[0026] (3) Then, boric acid is added and mixed, and the mixture is placed in a polytetrafluoroethylene digestion tank at a constant temperature and then dried in a blast drying oven, and washed with deionized water until neutral to obtain pretreated red pine raw material carbon;

[0027] (4) Pre-treating the raw red pine carbon under the protection of nitrogen, then removing the nitrogen and introducing water vapor for activation, closing the water vapor valve, then opening the nitrogen valve, cooling to room temperature to obtain water vapor activated red pine carbon, then adding distilled water and polyethyleneimine to mix and ultrasonically treating to form liquid red pine carbon;

[0028] (5) Add ethanol to liquid red pine carbon to form a mixed solution, then add ferrous sulfate heptahydrate while stirring, then add ferric chloride hexahydrate, add ammonia water to adjust the pH value after stirring, heat and stir, dry, and cool to obtain a high-efficiency adsorption injection activated carbon.

[0029] In the step (1), the drying temperature is 180° C., the sieving mesh size is 200 mesh, the temperature and time of the heat preservation carbonization are 300° C. and 1 hour respectively, and the temperature and time of the heat preservation activation are 400° C. and 2 hours respectively.

[0030] In the step (2), the mass ratio of the Korean pine raw carbon to potassium hydroxide is 2:1, the solid-liquid ratio of the total mass of the Korean pine raw carbon and potassium hydroxide to deionized water is 10:1 g / L, and the temperature and time of the constant temperature immersion are 20° C. and 20 h, respectively.

[0031] In the step (3), the solid-liquid ratio of carbon powder a to boric acid is 1:2 g / mL, wherein the mass concentration of boric acid is 8%, and the temperature and time of the constant temperature immersion are 40° C. and 8 h, respectively.

[0032] The heating in step (4) refers to heating to 700° C., and the activation time is 80 minutes.

[0033] In the step (4), the solid-liquid ratio of steam-activated red pine carbon to distilled water is 1:10 g / mL, the volume ratio of distilled water to polyethyleneimine is 100:0.05, and the ultrasonic time is 3 hours.

[0034] In step (5), the volume ratio of liquid red pine carbon to ethanol is 1.5:1, wherein the mass concentration of ethanol is 75%, and the mass contents of ferrous sulfate heptahydrate and ferric chloride hexahydrate in the mixed liquid are 3.0% and 8.2% respectively.

[0035] The molar concentration of the ammonia water in step (5) is 0.1 mol / L, the pH value is 7, and the time and temperature of the heating and stirring are 2 h and 80° C., respectively.

[0036] Example 2

[0037] A method for preparing highly efficient adsorption injection activated carbon, the method comprising the following steps:

[0038] (1) crushing red pine wood with a pulverizer, drying it in a drying oven, and then sieving it to obtain a raw material powder, placing the raw material powder in a fluidized bed, introducing nitrogen and heating it, heat-insulating it for carbonization, then replacing the nitrogen with carbon dioxide for heat-insulating activation, and cooling it to room temperature to obtain red pine raw material carbon;

[0039] (2) mixing red pine raw carbon with potassium hydroxide, adding deionized water and stirring to mix, impregnating in a polytetrafluoroethylene digestion tank at a constant temperature, and then drying in a blast drying oven, and then washing with deionized water until neutral and drying to obtain carbon powder a;

[0040] (3) Then, boric acid is added and mixed, and the mixture is placed in a polytetrafluoroethylene digestion tank at a constant temperature and then dried in a blast drying oven, and washed with deionized water until neutral to obtain pretreated red pine raw material carbon;

[0041] (4) Pre-treating the raw red pine carbon under the protection of nitrogen, then removing the nitrogen and introducing water vapor for activation, closing the water vapor valve, then opening the nitrogen valve, cooling to room temperature to obtain water vapor activated red pine carbon, then adding distilled water and polyethyleneimine to mix and ultrasonically treating to form liquid red pine carbon;

[0042] (5) Add ethanol to liquid red pine carbon to form a mixed solution, then add ferrous sulfate heptahydrate while stirring, then add ferric chloride hexahydrate, add ammonia water to adjust the pH value after stirring, heat and stir, dry, and cool to obtain a high-efficiency adsorption injection activated carbon.

[0043] In the step (1), the drying temperature is 190° C., the sieving mesh size is 250 mesh, the temperature and time of the heat preservation carbonization are 450° C. and 1.5 h respectively, and the temperature and time of the heat preservation activation are 450° C. and 2 h respectively.

[0044] In the step (2), the mass ratio of the Korean pine raw carbon to potassium hydroxide is 3:1, the solid-liquid ratio of the total mass of the Korean pine raw carbon and potassium hydroxide to deionized water is 30:1 g / L, and the temperature and time of the constant temperature immersion are 25° C. and 22.5 h, respectively.

[0045] In the step (3), the solid-liquid ratio of carbon powder a to boric acid is 1:3 g / mL, wherein the mass concentration of boric acid is 8%, and the temperature and time of the constant temperature immersion are 45° C. and 9 h, respectively.

[0046] The heating in step (4) refers to heating to 800° C., and the activation time is 90 minutes.

[0047] In the step (4), the solid-liquid ratio of steam-activated red pine carbon to distilled water is 1:10 g / mL, the volume ratio of distilled water to polyethyleneimine is 100:0.08, and the ultrasonic time is 4 hours.

[0048] In step (5), the volume ratio of liquid red pine carbon to ethanol is 1.5:1, wherein the mass concentration of ethanol is 75%, and the mass contents of ferrous sulfate heptahydrate and ferric chloride hexahydrate in the mixed liquid are 3.3% and 8.4% respectively.

[0049] The molar concentration of the ammonia water in the step (5) is 0.1 mol / L, the pH value is 7, and the time and temperature of the heating and stirring are 2.5 h and 90° C. respectively.

[0050] Example 3

[0051] A method for preparing highly efficient adsorption injection activated carbon, the method comprising the following steps:

[0052] (1) crushing red pine wood with a pulverizer, drying it in a drying oven, and then sieving it to obtain a raw material powder, placing the raw material powder in a fluidized bed, introducing nitrogen and heating it, heat-insulating it for carbonization, then replacing the nitrogen with carbon dioxide for heat-insulating activation, and cooling it to room temperature to obtain red pine raw material carbon;

[0053] (2) mixing red pine raw carbon with potassium hydroxide, adding deionized water and stirring to mix, impregnating in a polytetrafluoroethylene digestion tank at a constant temperature, and then drying in a blast drying oven, and then washing with deionized water until neutral and drying to obtain carbon powder a;

[0054] (3) Then, boric acid is added and mixed, and the mixture is placed in a polytetrafluoroethylene digestion tank at a constant temperature and then dried in a blast drying oven, and washed with deionized water until neutral to obtain pretreated red pine raw material carbon;

[0055] (4) Pre-treating the raw red pine carbon under the protection of nitrogen, then removing the nitrogen and introducing water vapor for activation, closing the water vapor valve, then opening the nitrogen valve, cooling to room temperature to obtain water vapor activated red pine carbon, then adding distilled water and polyethyleneimine to mix and ultrasonically treating to form liquid red pine carbon;

[0056] (5) Add ethanol to liquid red pine carbon to form a mixed solution, then add ferrous sulfate heptahydrate while stirring, then add ferric chloride hexahydrate, add ammonia water to adjust the pH value after stirring, heat and stir, dry, and cool to obtain a high-efficiency adsorption injection activated carbon.

[0057] In the step (1), the drying temperature is 200° C., the sieving mesh size is 300 meshes, the temperature and time of the heat preservation carbonization are 600° C. and 2 h respectively, and the temperature and time of the heat preservation activation are 500° C. and 2 h respectively.

[0058] In the step (2), the mass ratio of the Korean pine raw carbon to potassium hydroxide is 4:1, the solid-liquid ratio of the total mass of the Korean pine raw carbon and potassium hydroxide to deionized water is 50:1 g / L, and the temperature and time of the constant temperature immersion are 30° C. and 24 h, respectively.

[0059] In the step (3), the solid-liquid ratio of carbon powder a to boric acid is 1:4 g / mL, wherein the mass concentration of boric acid is 8%, and the temperature and time of the constant temperature immersion are 50° C. and 10 h, respectively.

[0060] The heating in step (4) refers to heating to 900° C., and the activation time is 100 minutes.

[0061] In the step (4), the solid-liquid ratio of steam-activated red pine carbon to distilled water is 1:10 g / mL, the volume ratio of distilled water to polyethyleneimine is 100:1, and the ultrasonic time is 5 hours.

[0062] In step (5), the volume ratio of liquid red pine carbon to ethanol is 1.5:1, wherein the mass concentration of ethanol is 75%, and the mass contents of ferrous sulfate heptahydrate and ferric chloride hexahydrate in the mixed liquid are 3.5% and 8.5% respectively.

[0063] The molar concentration of the ammonia water in the step (5) is 0.1 mol / L, the pH value is 7, and the time and temperature of the heating and stirring are 3 h and 100° C. respectively.

[0064] Comparative Example 1

[0065] On the basis of Example 2, a method for preparing highly efficient adsorption injection activated carbon is provided, wherein the method for preparing highly efficient adsorption injection activated carbon comprises the following steps:

[0066] (1) crushing red pine wood with a pulverizer, drying it in a drying oven, and then sieving it to obtain a raw material powder, placing the raw material powder in a fluidized bed, introducing nitrogen and heating it, heat-insulating it for carbonization, then replacing the nitrogen with carbon dioxide for heat-insulating activation, and cooling it to room temperature to obtain red pine raw material carbon;

[0067] (2) mixing red pine raw carbon with potassium hydroxide, adding deionized water and stirring to mix, impregnating in a polytetrafluoroethylene digestion tank at a constant temperature, and then drying in a blast drying oven, and then washing with deionized water until neutral and drying to obtain carbon powder a;

[0068] (3) Then, boric acid is added and mixed, and the mixture is placed in a polytetrafluoroethylene digestion tank at a constant temperature and then dried in a blast drying oven, and washed with deionized water until neutral to obtain pretreated red pine raw material carbon;

[0069] (4) adding distilled water and polyethyleneimine to the pretreated red pine raw carbon and mixing them for ultrasonic treatment to form liquid red pine carbon;

[0070] (5) Add ethanol to liquid red pine carbon to form a mixed solution, then add ferrous sulfate heptahydrate while stirring, then add ferric chloride hexahydrate, add ammonia water to adjust the pH value after stirring, heat and stir, dry, and cool to obtain a high-efficiency adsorption injection activated carbon.

[0071] In the step (1), the drying temperature is 190° C., the sieving mesh size is 250 mesh, the temperature and time of the heat preservation carbonization are 450° C. and 1.5 h respectively, and the temperature and time of the heat preservation activation are 450° C. and 2 h respectively.

[0072] In the step (2), the mass ratio of the Korean pine raw carbon to potassium hydroxide is 3:1, the solid-liquid ratio of the total mass of the Korean pine raw carbon and potassium hydroxide to deionized water is 30:1 g / L, and the temperature and time of the constant temperature immersion are 25° C. and 22.5 h, respectively.

[0073] In the step (3), the solid-liquid ratio of carbon powder a to boric acid is 1:3 g / mL, wherein the mass concentration of boric acid is 8%, and the temperature and time of the constant temperature immersion are 45° C. and 9 h, respectively.

[0074] In the step (4), the solid-liquid ratio of the pretreated Korean pine raw material carbon to distilled water is 1:10 g / mL, the volume ratio of distilled water to polyethyleneimine is 100:0.08, and the ultrasonic time is 4 hours.

[0075] In step (5), the volume ratio of liquid red pine carbon to ethanol is 1.5:1, wherein the mass concentration of ethanol is 75%, and the mass contents of ferrous sulfate heptahydrate and ferric chloride hexahydrate in the mixed liquid are 3.3% and 8.4% respectively.

[0076] The molar concentration of the ammonia water in the step (5) is 0.1 mol / L, the pH value is 7, and the time and temperature of the heating and stirring are 2.5 h and 90° C. respectively.

[0077] Comparative Example 2

[0078] On the basis of Example 2, a method for preparing highly efficient adsorption injection activated carbon is provided, wherein the method for preparing highly efficient adsorption injection activated carbon comprises the following steps:

[0079] (1) crushing red pine wood with a pulverizer, drying it in a drying oven, and then sieving it to obtain a raw material powder, placing the raw material powder in a fluidized bed, introducing nitrogen and heating it, heat-insulating it for carbonization, then replacing the nitrogen with carbon dioxide for heat-insulating activation, and cooling it to room temperature to obtain red pine raw material carbon;

[0080] (2) mixing red pine raw carbon with potassium hydroxide, adding deionized water and stirring to mix, impregnating in a polytetrafluoroethylene digestion tank at a constant temperature, and then drying in a blast drying oven, and then washing with deionized water until neutral and drying to obtain carbon powder a;

[0081] (3) Then, boric acid is added and mixed, and the mixture is placed in a polytetrafluoroethylene digestion tank at a constant temperature and then dried in a blast drying oven, and washed with deionized water until neutral to obtain pretreated red pine raw material carbon;

[0082] (4) The pre-treated red pine raw carbon was heated under the protection of nitrogen, and then the nitrogen was removed and water vapor was introduced for activation. The water vapor valve was closed and the nitrogen valve was opened. The carbon was cooled to room temperature to obtain a highly efficient adsorption injection activated carbon.

[0083] In the step (1), the drying temperature is 190° C., the sieving mesh size is 250 mesh, the temperature and time of the heat preservation carbonization are 450° C. and 1.5 h respectively, and the temperature and time of the heat preservation activation are 450° C. and 2 h respectively.

[0084] In the step (2), the mass ratio of the Korean pine raw carbon to potassium hydroxide is 3:1, the solid-liquid ratio of the total mass of the Korean pine raw carbon and potassium hydroxide to deionized water is 30:1 g / L, and the temperature and time of the constant temperature immersion are 25° C. and 22.5 h, respectively.

[0085] In the step (3), the solid-liquid ratio of carbon powder a to boric acid is 1:3 g / mL, wherein the mass concentration of boric acid is 8%, and the temperature and time of the constant temperature immersion are 45° C. and 9 h, respectively.

[0086] The heating in step (4) refers to heating to 800° C., and the activation time is 90 minutes.

[0087] Comparative Example 3

[0088] On the basis of Example 2, in the preparation process of high-efficiency adsorption injection activated carbon, the impregnation with boric acid is replaced by impregnation with hydrochloric acid, wherein the mass concentration of the hydrochloric acid is 35%, and the other conditions remain the same as in Example 2.

[0089] Performance Testing

[0090] 1. The highly adsorbent activated carbon for injection prepared in Examples 1-3 and Comparative Examples 1-3 was tested for methylene blue adsorption value according to GB / T12496.10-1999, for quinine sulfate adsorption value according to GB / T12496.11-1999, and for ash content according to GB / T12496.3-1999.

[0091] The test results are shown in Table 1.

[0092] Table 1 Test results

[0093]

[0094] As can be seen from Table 1, the methylene blue adsorption value and quinine sulfate adsorption value of Examples 1-3 are greater than those of Comparative Example 1, and the ash content is less than that of Comparative Example 1. Comparative Example 1 is activated by water vapor, and the adsorption performance is less than that of the example; Comparative Example 2 is not loaded with iron ions, and the activity of the activated carbon is less than that of the example; Comparative Example 3 uses hydrochloric acid instead of boric acid, and its strong acidity causes collapse of the pore structure, reduces the porosity, and thus the adsorption effect is worse than that of the example.

[0095] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing highly efficient adsorption injection activated carbon, characterized in that: The preparation method of the highly efficient adsorption injection activated carbon comprises the following steps: (1) crushing red pine wood with a pulverizer, drying it in a drying oven, and then sieving it to obtain a raw material powder, placing the raw material powder in a fluidized bed, introducing nitrogen and heating it, heat-insulating it for carbonization, then replacing the nitrogen with carbon dioxide for heat-insulating activation, and cooling it to room temperature to obtain red pine raw material carbon; (2) mixing red pine raw carbon with potassium hydroxide, adding deionized water and stirring to mix, impregnating in a polytetrafluoroethylene digestion tank at a constant temperature, and then drying in a blast drying oven, and then washing with deionized water until neutral and drying to obtain carbon powder a; (3) Then, boric acid is added and mixed, and the mixture is placed in a polytetrafluoroethylene digestion tank at a constant temperature and then dried in a blast drying oven, and washed with deionized water until neutral to obtain pretreated red pine raw material carbon; The solid-liquid ratio of the carbon powder a to boric acid is 1:2-4 g / mL, wherein the mass concentration of boric acid is 8%; (4) Pre-treating the raw red pine carbon under the protection of nitrogen, then removing the nitrogen and introducing water vapor for activation, closing the water vapor valve, then opening the nitrogen valve, cooling to room temperature to obtain water vapor activated red pine carbon, then adding distilled water and polyethyleneimine to mix and ultrasonically treating to form liquid red pine carbon; The heating refers to heating to 700-900°C, and the activation time is 80-100min; the solid-liquid ratio of the steam-activated red pine carbon to distilled water is 1:10g / mL, the volume ratio of distilled water to polyethyleneimine is 100:0.05-1, and the ultrasonic time is 3-5h; (5) adding ethanol to liquid red pine carbon to form a mixed solution, then adding ferrous sulfate heptahydrate while stirring, then adding ferric chloride hexahydrate, stirring, adding ammonia water to adjust the pH value, heating and stirring, drying, and cooling to obtain a high-efficiency adsorption injection activated carbon; The mass contents of the ferrous sulfate heptahydrate and the ferric chloride hexahydrate in the mixed solution are 3.0-3.5% and 8.2-8.5% respectively.

2. The method for preparing a highly efficient adsorption injection activated carbon according to claim 1, characterized in that: In the step (1), the drying temperature is 180-200° C., the sieving mesh size is 200-300 mesh, the temperature and time of the heat preservation carbonization are 300-600° C. and 1-2 h respectively, and the temperature and time of the heat preservation activation are 400-500° C. and 2 h respectively.

3. The method for preparing a highly efficient adsorption injection activated carbon according to claim 1, characterized in that: In the step (2), the mass ratio of the Korean pine raw carbon to potassium hydroxide is 2-4:1, the solid-liquid ratio of the total mass of the Korean pine raw carbon and potassium hydroxide to deionized water is 10-50:1 g / L, and the temperature and time of the constant temperature immersion are 20-30°C and 20-24h respectively.

4. The method for preparing a highly efficient adsorption injection activated carbon according to claim 1, characterized in that: The temperature and time of the constant temperature immersion in step (3) are 40-50° C. and 8-10 h respectively.

5. The method for preparing a highly efficient adsorption injection activated carbon according to claim 1, characterized in that: In the step (5), the volume ratio of liquid red pine carbon to ethanol is 1.5:1, wherein the mass concentration of ethanol is 75%.

6. The method for preparing a highly efficient adsorption injection activated carbon according to claim 1, characterized in that: In the step (5), the molar concentration of the ammonia water is 0.1 mol / L, the pH value is 7, and the time and temperature of the heating and stirring are 2-3 h and 80-100° C., respectively.

Citation Information

Patent Citations

  • Method for preparing active carbon for relieving or neutralizing effect of alcohol

    CN103043661A

  • Method for preparing ionic liquid-loaded traditional Chinese medicine residue activated carbon

    CN107128912A